Effect of fumed silica and halloysite nanoparticles on the microstructure, mechanical, and fracture properties of thermoplastic polyolefin elastomer toughened polypropylene. Issue 7 (26th May 2022) - Rajaee, Pouya; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad; Sadeghi, Alireza; Kakeh, Behnam
Abstract: In this article, mechanical and fracture properties of two types of nanoparticles, namely fumed silica (FS) and halloysite nanotube filled polypropylene (PP) toughened with two types of thermoplastic elastomers (TPOs), namely ethylene‐based TPO (ETPO) and propylene‐based TPO (PTPO) were investigated. A full factorial design was exploited to clarify the influence of each factor as well as its interaction on outcomes. The essential work of fracture (EWF) approach was utilized to study the effect of each factor on fracture behavior. The addition of TPO enhanced the elongation at break and non‐EWF by 62% and 40%, in turn. In addition, the tensile strength, modulus, and EWF increased by 8%, 34%, and 7%, respectively, by increasing the nanoparticles up to 1 wt%. The blend nanocomposite with 10 wt% of PTPO and 1 wt% of FS was selected as the best stiffness‐ toughness‐strength equivalence based on optimization results. Additionally, the R 2 extracted from the analysis of variance (ANOVA) and plots of normal probability indicated good agreement between the experimental data and for foreseen one using full factorial models.